DISTRIBUTION ANALYSIS AND PROSPECTS OF PRE TAF CARBONATE ROCKS IN CCC FIELD, NORTH WEST JAVA BASIN, INDONESIA - Crysta Chandra, Clarissa
The North West Java Basin is one of the largest hydrocarbon-producing basins in Indonesia. All conventional prospects targeting the Parigi, Cibulakan, Baturaja, and Talang Akar Formation have been explored and produced. Based on regional chronostratigraphic correlations, a carbonate interval of Eocene age was found called the Pre Talang Akar Formation (Pre TAF) which is a new play in the North West Java Basin. This carbonate interval has proven to be one of the reservoirs, where one of the drilled wells, namely CL-2, has produced hydrocarbons. This indicates that the carbonate interval under the Talang Akar Formation is a new interval target that is very interesting to investigate in this basin. The methodology used in this study is divided into several stages, namely: Identifying the characteristics of Pre TAF carbonates. Calculating petrophysical properties to see reservoir quality. Mapping the distribution of Pre TAF carbonate using 3D seismic data and five well data. Mapping the distribution of fractures and faults using image log and ant-track seismic attributes. The results are integrated to search potential reservoirs in Pre TAF carbonates. Based on the results of the core data analysis, there are differences in the characteristics of the Pre TAF carbonate rock of the two wells that have core data, namely well CL-1 and well CL-5. The carbonate rock in well CL-1 is white limestone while the carbonate rock in well CL-5 is black limestone because it is rich in organic matter, this is due to the presence of a horst that separates the two wells. The results of petrophysical calculations show that the porosity of the rock tends to be not good (tight). The increase in carbonate porosity was caused by brecciated zone caused by fault which were validated by image log, namely 1.3% - 9%. Based on the analysis, the distribution of fractures in well in the direction of the main fault with the NNE-SSW direction is also seen in the ant track attribute. From the results of the carbonate mapping, there were 11 build up carbonates Three of the build up carbonates have been drilled. The results of all data integration show that there are five carbonate build up prospects in the study area.